Scattering phase delay and momentum transfer of light in disordered media - Pavel Yazhgur; Geoffroy J. Aubry; Luis S. Froufe-Pérez; Frank Scheffold (Physical Review Research, 2022)
Disordered dielectric materials with short-range spatial correlations on length scales comparable to the wavelength of light display a rich variety of optical phenomena: photonic band gaps, structural coloring, strong scattering, and whiteness. However, a lack of reliable and straightforward analytical models complicates the rationale design of optical materials for specific applications. Here, we demonstrate how to accurately introduce collective scattering and define the effective medium in single scattering from heterogeneous dielectrics with a substantial refractive index contrast, starting from fundamental principles. Our model captures the effective medium's role in the momentum transfer definition for the particle form and structure factor in the forward scattering regime. We support our claims through transfer matrix calculations scattering from particle clusters.